Determinan Kinerja Keuangan dengan Size sebagai Pemoderasi pada Perusahaan Food and Beverages yang Terdaftar di BEI - Dini Indah Prasasti; Nurjanti Takarini (IPM2KPE, 2022)
This study aims to understand the effect of liquidity ratios and solvency ratios on financial performance with size as a moderator for food and beverages companies listed on the Indonesia Stock Exchange in 2017-2020. This research method is descriptive quantitative. The research sample was determined using a purposive sampling technique with a total sample of 17 food and beverages companies listed on the IDX in 2017-2020. The analysis method used in this research is Moderated Regression Analysis. Hypothesis testing was carried out using a partial test (t test) and a simultaneous test (F test). The results show, a) the current ratio has no effect on financial performance; b) DER has an effect on financial performance; c) company size is unable to moderate the effect of liquidity on financial performance; d) while the size of the company is able to moderate the effect of solvency on financial performance. In conclusion, a) liquidity does not contribute to the financial performance of food and beverages companies listed on the Indonesia Stock Exchange in 2017-2020; b) solvency contributes to the financial performance of food and beverages companies listed on the Indonesia Stock Exchange in 2017-2020; c) company size cannot moderate the relationship between liquidity and financial performance in food and beverages companies listed on the Indonesia Stock Exchange in 2017-2020; d) company size can moderate the relationship between solvency and financial performance in food and beverages companies listed on the Indonesia Stock Exchange in 2017-2020. Keywords: Financial Performance, Liquidity, Solvency, Firm Size